﻿Signal transducers and activators of transcription protein 1 (STAT1) is activated in macrophages by Zymosan through Dectin-1 - Cuong, Trinh Tat; Nghia, Phan Tuan; Chinh, Vu Tien (Academia Journal of Biology, 2012)
﻿Zymosan, an insoluble preparation of yeast cell, has been shown to recognized by Dectin-1, a phagocytic receptor expressed on macrophages and dendritic cells, which collaborates with toll-like receptor (TLR) 2 and ﻿TLR6 enhancing the immune responses triggered by the recognition of zymosan by each receptor. Although zymosan has been reported as a target molecule for TLR signaling, the role(s) of signal transducers and activators of transcription protein (STAT) 1 on the innate immune responses induced by zymosan remain elusive. In the present study, we investigate the role of STAT1 on the zymosan-induced production of proinflammatory cytokines by murine bone marrow-derived macrophages (BMDMs). Zymosan-induced proinflammatory cytokine production was dependent on the activation of STAT1, because the mRNA of cytokines and chemokines were totally abrogated in STAT1-deficient BMDMs. In addition, zymosan actively induced the activation of STAT1 through both Tyr-701 and Ser-727 phosphorylation by BMDMs. Furthermore, Dectin-1 was required for zymosan-induced STAT1 activation in macrophages. Taken together, these results indicate that STAT1 activation plays an essential role in the induction of innate immune responses to zymosan-induced innate immune responses via Dectin-1.